Growth and reproductive performance of meat goats in northern Tanzania - Bee, J.K.A.; Said, R.; Mushi, M.S.; Saideiya, P.D.; Mbeyela, T. (Small Ruminant Collaborative Research Support Program, 1992)
Factors affecting growth and reproductive performance of Blended and Galla goats at the Livestock Research Centre, West Kilimanjaro were investigated. Data and discussions of the results in relation to reports on meat goats elsewhere in the tropics, live weight, daily gain and reproductive parameters of meat goats included.